Education for the people: Concepts of Grundtvig, Tagore, Gandhi and Freire. Translated by John Stanley Martin - Wåhlin, Vagn; Pedersen, Kim Arne (Grundtvig-Studier, 2008)
Uddannelse for folk: Koncept af Grundtvig, Tagore, Gandhi og Freire. Anmeldt af Vagn Wåhling og Kim Arne Pedersen; oversat af John Stanley Martin